(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The present study has beendesigned to investigate the relationship and contribution of Emotional maturityin the academic achievement of highschool students along with other variables like general mental ability, socialmaturity, tolerance and anxiety and alsoto see the sex and regional differenceson the basis of their emotional maturity. The study was conducted over a sampleof 400 (200 boys and 200 girls) high school students studying in X class indifferent schools (4 urban and 4 rural) of Gujarat. Singh & Bhargava’sEmotional maturity scale, Ahuja’s group test of intelligence, Rao’s Socialmaturity scale and Sharma’s general anxiety scale for children, were employedto measure students’ Emotional maturity, general mental ability, socialmaturity and anxiety and the aggregate score of the selected students in theboard examinations was taken to show their level of academic achievement. Theresults reported that emotional maturity played no significant role in theacademic achievement of high school students in a given set of variables. Nosignificant differences were observed between boys and girls as well as ruraland urban students on the basis of their emotional maturity.